The Effect of Corporate Social Responsibility Disclosure and Good Corporate Governance on Financial Performance (Study on Mining Sector Companies Listed on the Indonesia Stock Exchange in 2020–2024) - Khansa Rayhan Dhirayoga; Wiwin Aminah (DINASTI RESEARCH, 2025)
This study examines the effect of Corporate Social Responsibility Disclosure (CSRD) and Good Corporate Governance (GCG) on financial performance for mining firms listed on the Indonesia Stock Exchange during 2020–2024. The sample includes 12 companies yielding 60 panel observations. Financial performance is proxied by Return on Assets (ROA). Independent variables are CSRD, board size, proportion of independent commissioners, and audit committee size. Panel regression analysis (Common Effect Model) was applied using EViews 12. Results show that CSRD and GCG jointly affect financial performance (Prob F = 0.000123). Individually, CSRD and board size have positive significant effects on ROA, independent commissioners have a significant negative effect, while audit committee size is not significant. The findings highlight the role of CSR disclosure and board effectiveness in improving profitability and suggest evaluating the oversight quality of commissioners and audit committees to enhance governance outcomes.